On a New Insular Subspecies of Chrysozephyrus mushaellus (Matsumura) (Lepidoptera: Lycaenidae) Discovered from Hainan - Hsu, Yu-Feng; Lo, Yik-Fui Philip; Lin, Rung-Juen (Zootaxa, 2021)
Chrysozephyrus mushaellus paolongkoui, ssp. nov. is described and illustrated from Hainan island of southern China. This new subspecies possesses diagnosable characters different from previously recognized subspecies of C. mushaellus in wing marking and genitalia of both sexes. It utilizes Lithocarpus litseifolius (Fagaceae) as the larval hostplant.